Im/SM Essentials of Economics - Mankiw, Gregory N. (Cengage Learning, Inc, 2007)
For queries and grading, the Instructor's Manual contains solutions to exercises from the textbook. Dean Croushore (university of Richmond) prepared many of the solutions for the "Quick Quizzes," " Question for Review," and "Problems and Applications" found in the textbook